Workplace Impact of Social Networking in Nepalese Organization - Paudel, Prashant (Nepalese Journal of Management, 2025)
This study examines the workplace impact of social networking in Nepalese organization. Employee performance is selected as the dependent variable. Similarly, turnover intention, job satisfaction, social network participation, communication, organizational structure are selected as the dependent variables. This study is based on primary data with 121 observation. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing workplace impact of social networking in Nepalese organization. The study showed that that the communication has a positive impact on employee performance. It means that better the communication, better would be the employee performance. Similarly, turnover intention has a negative impact on employee performance. It means that increase in turnover intention leads to decrease in employee performance. Moreover, the job satisfaction has a positive impact on employee performance. It indicates that increase in job satisfaction leads to increase in employee performance. In addition, the social network participation has a positive impact on employee performance. It indicates that increase in social network participation leads to increase in employee performance. Likewise, the organizational structure has a positive impact on employee performance. It means that better the organizational structure, better would be the employee performance.